[P198] Cone beam CT as a clinical QA tool for prostate MRI-only workflows. (August 2018) - Palmér, Emilia; Persson, Emilia; Ambolt, Petra; Gustafsson, Christian; Gunnlaugsson, Adalsteinn; Olsson, Lars E.
Abstract : Purpose: Magnetic resonance imaging (MRI) only radiotherapy has in recent years been introduced as a clinical workflow for prostate cancer patients. MRI only radiotherapy is performed without computed tomography (CT) and instead, a synthetic CT (sCT) is used for treatment planning. With the introduction of new procedures for treatment planning, development of quality assurance (QA) tools must be considered. Today, no such tool has yet been presented. The aim of this study was to develop a clinically feasible QA procedure for sCT using the kV-cone beam CT (CBCT), in an MRI-only workflow for prostate cancer patients. Methods: Three criteria were addressed; 1. Stability in Hounsfield Units (HUs), 2. Deviations in HUs between the CT and CBCT and 3. Validation of the QA procedure. For the two first criteria, phantom measurements were performed. For the third criteria, sCT, CT and CBCT for ten patients were used. Treatment plans were created based on the sCT (MriPlanner TM ). CT and CBCT images were registered to the sCT. The treatment plan was recalculated on the CT and CBCT. Dose-volume histogram (DVH) metrics were used to evaluate dosimetric differences between the sCT plan and the recalculated CT and CBCT plans. Well defined errors were artificially introduced in the sCT for one patient to evaluate efficacy of the QA procedure. Results: The kV-CBCT system was stable in HU over time (SD <40 HU). Difference in HUs between CT and CBCT was very small (<60 HU). The differences between sCT-CT and sCT-CBCT dose distributions were below or equal to 1.0%. The highest mean dose difference for the CT and CBCT dose distribution was 0.6%. No statistically significant difference was found between total mean dose deviations from recalculated CT and CBCT plans, except for femoral head. The proposed QA method was found very helpful in identifying the introduced errors. Conclusions: The results in this study indicates that CBCT can be used as a clinically feasible QA tool for MRI-only radiotherapy of prostate cancer patients. The proposed method could easily be integrated in any modern image guided radiotherapy workflow without extensive work.